Autogenic Relaxation as a Form of Non-Pharmacological Supportive Intervention for Headaches in Hypertensive Patients - Diah Priyantini; Noryani Noryani; Suyatno Hadi Saputro; Retno Sumara; Daviq Ayatulloh (Universitas Muhammadiyah Surabaya, 2026)
Hypertension is a major public health problem and is frequently associated with headache, which can significantly interfere with daily activities. Pharmacological therapy remains the most common treatment; however, long-term use may lead to side effects and reduced adherence. Therefore, non-pharmacological supportive therapies, such as autogenic relaxation, are increasingly considered as alternative approaches. This study aimed to evaluate the effectiveness of autogenic relaxation therapy in reducing headache intensity among patients with hypertension. This research employed a case intervention approach conducted at a community health center in Surabaya, Indonesia. Four patients diagnosed with hypertension participated in the study. Data collection was carried out through home visits, including interviews, observation, and review of health history over the past six months. Blood pressure was measured using a tensiometer, and headache intensity was assessed using the Numeric Rating Scale (NRS) and PQRST method. Participants were guided to perform autogenic relaxation therapy twice weekly and independently at home for 20 minutes per session. The results demonstrated that all participants initially experienced moderate headache intensity (NRS 4–6). After the intervention, there was a consistent reduction in pain levels, with all participants reporting mild headache intensity (NRS 2–3). The most notable reduction was observed after the second session of therapy, indicating a progressive improvement in pain control. In conclusion, autogenic relaxation therapy is effective in reducing headache intensity among patients with hypertension. This non-pharmacological approach can be considered a simple, safe, and accessible intervention to complement conventional treatment and improve patient well-being.